Association of noninvasive quantitative decline in liver fat content on MRI with histologic response in nonalcoholic steatohepatitis. (September 2016) - Patel, Janki; Bettencourt, Ricki; Cui, Jeffrey; Salotti, Joanie; Hooker, Jonathan; Bhatt, Archana; Hernandez, Carolyn; Nguyen, Phirum; Aryafar, Hamed; Valasek, Mark; Haufe, William; Hooker, Catherine; et al.
Background: Magnetic resonance imaging-estimated proton-density-fat-fraction (MRI-PDFF) has been shown to be a noninvasive, accurate and reproducible imaging-based biomarker for assessing steatosis and treatment response in nonalcoholic steatohepatitis (NASH) clinical trials. However, there are no data on the magnitude of MRI-PDFF reduction corresponding to histologic response in the setting of a NASH clinical trial. The aim of this study was to quantitatively compare the magnitude of MRI-PDFF reduction between histologic responders versus histologic nonresponders in NASH patients. Methods: This study is a secondary analysis of the MOZART trial, which included 50 patients with biopsy-proven NASH randomized to ezetimibe 10 mg/day orally or placebo for 24 weeks. The primary aim was to perform a head-to-head comparative analysis of histologic responders [defined as a ⩾2-point reduction in the nonalcoholic fatty liver disease (NAFLD) Activity Score (NAS) without worsening fibrosis] versus nonresponders, and the corresponding quantitative change in liver fat content measured via MRI-PDFF. Results: Of the 35 patients who underwent paired liver biopsy and MRI-PDFF assessment at the beginning and end of treatment, 10 demonstrated a histologic response. Compared with histologic nonresponders, histologic responders had a statistically significant reduction in MRI-PDFF of −4.1% ± 4.9 versus −0.6 ± 4.1 ( p < 0.04) with a mean relative percent change of −29.3% ± 33.0 versus +2.0% ± 24.0 ( p < 0.004), respectively. Conclusions: Utilizing paired MRI-PDFF and liver histology data, we demonstrate that a relative reduction of 29% in liver fat on MRI-PDFF is associated with a histologic response in NASH. After external validation by independent research groups, these results can be incorporated into designing future NASH clinical trials, especially those utilizing change in hepatic fat quantified by MRI-PDFF, as a treatment endpoint.